Postbloom Fruit Drop (PFD) Identification and Management - Megan M. Dewdney; Natalia A. Peres; Jamie D. Burrow (EDIS, 2015)
This two-sided ID card is ideal for growers working in the field trying to identify or manage postbloom fruit drop (PFD) in citrus. The ID card includes photos of blooms affected by PFD and photos of healthy blooms for comparison. The card also includes facts and tips for managing PFD. Written by Megan M. Dewdney, Natalia A. Peres, and Jamie D. Burrow, and published by the UF Department of Plant Pathology, July 2015.